2004
DOI: 10.1523/jneurosci.4485-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Function of the PGE2EP2 Receptor in Cerebral Ischemia

Abstract: The cyclooxygenases COX-1 and COX-2 catalyze the first committed step of prostaglandin synthesis from arachidonic acid. Previous studies in rodent stroke models have shown that the inducible COX-2 isoform promotes neuronal injury, and the administration of COX-2 inhibitors reduces infarct volume. We investigated the function of PGE 2 , a principal prostaglandin product of COX-2 enzymatic activity, in neuronal survival in cerebral ischemia. PGE 2 exerts its downstream effects by signaling through a class of fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
377
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(401 citation statements)
references
References 103 publications
20
377
4
Order By: Relevance
“…Various studies related to the protective role of prostaglandin E 2 receptors in paradigms of neuronal toxicity or animal models of neurodegeneration have indicated a potential role for increasing intracellular levels of cAMP and its downstream MAP kinase or protein kinase signaling pathways (McCullough et al 2004;Echeverria et al 2005;Ahmad et al 2006c). In parallel with these reports, Liang et al (2005) showed that DP1 receptor agonist BW245C protects against glutamate toxicity in cultured hippocampal neurons and organotypic slices in a cAMP-dependent fashion; they also showed that neurotoxic effects produced by glutamate in dispersed hippocampal neurons were abolished by protein kinase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies related to the protective role of prostaglandin E 2 receptors in paradigms of neuronal toxicity or animal models of neurodegeneration have indicated a potential role for increasing intracellular levels of cAMP and its downstream MAP kinase or protein kinase signaling pathways (McCullough et al 2004;Echeverria et al 2005;Ahmad et al 2006c). In parallel with these reports, Liang et al (2005) showed that DP1 receptor agonist BW245C protects against glutamate toxicity in cultured hippocampal neurons and organotypic slices in a cAMP-dependent fashion; they also showed that neurotoxic effects produced by glutamate in dispersed hippocampal neurons were abolished by protein kinase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…At end-ischemia, the animal was briefly reanaesthetized and reperfusion was initiated by filament withdrawal. Monitoring of physiological variables and laser Doppler flowmetry (LDF) was performed in companion cohorts for all groups as previously described (n ¼ 5/ group in all genotypes and pharmacological cohorts; McCullough et al, 2004;Sawada et al, 2000).…”
Section: Ischemic Modelmentioning
confidence: 99%
“…Infarct size was expressed as a percentage of the contralateral hemisphere/structure after correcting for edema (McCullough et al, 2004;Sawada et al, 2000).…”
Section: Terminal Histopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…indicating that the presence of meloxicam, probably acting on COX-2 inhibition, results in a neuroprotective effect on different models of cerebral ischemia (Nakayama et al, 1998;McCullough et al, 2004;Fathali et al, 2010), where glutamate excitotoxicity plays a critical role (Lipton, 1999;Campos et al, 2011). COX-2 has been hypothesized to attenuate glutamate excitotoxicity and, consequently, Ca 2+ influx, by indirectly modulating transcription of the ionotropic glutamatergic AMPA/KA and NMDA receptors based on COX-2-deficient mice assays (Caracciolo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%